FETOTOMY USING SURGICAL BLADE FOR RELIEVING DYSTOCIA DUE TO FETAL ARTHROGRYPOSIS IN EWE - RAJA, S; VIJAYARAJAN, A; SIAKUMAR, A; SATHESH KUMAR, S; PRABAHARAN, V; JAYAGANTHAN, P (The Indian Journal of Animal Reproduction, 2016)
A full term ewe was presented with fetus in anterior longitudinal presentation, dorso-sacral position, right unilateralshoulder flexion and absence of fetal reflex. The amputation of head, and ankylosed fore and hindlimbs was carriedout using scalpel and blade for per-vaginal delivery.
Keywords: Dystocia; Fetal arthrogryposis; Fetotomy; Sheep